Analysis and Forecast of the Shift From Double Control of Energy Consumption to Double Control of Carbon Emissions in Xinjiang - LI Changling; CHANG Xiqiang; LU Hao (发电技术)
ObjectivesAs a national energy base,the shift in energy policy in Xinjiang is of great significance to the realization of national energy strategy goals. The shift from controlling total amount and intensity of energy consumption to controlling total amount and intensity of carbon emissions in Xinjiang was investigated.MethodsTwo decoupling elasticity indexes of economic elasticity and energy consumption elasticity of carbon emissions were proposed, and the decoupling relationship between energy consumption and carbon emissions in Xinjiang was predicted.ResultsIt is found that Xinjiang has initially realized the relative decoupling of energy consumption and carbon emissions,and is expected to realize the absolute decoupling of energy consumption and carbon emissions in 2032. The shift in the dual-control index helps to improve the electrification level of end-use energy consumption in Xinjiang, but the pressure to maintain electricity supply increases.ConclusionsThe research results have guiding significance for energy policy making in Xinjiang and even the whole country, provide an empirical basis for realizing the goal of carbon neutrality, and also provide a reference for the transition path of other energy bases.